Inside Front Cover: Volume 1 Issue 1. Issue 1 (31st January 2022) - Unknown
Abstract : Inside Front Cover : Bi2 Te3 ‐based films are well known for their outstanding thermoelectric (TE) performance as highly efficient TE coolers and as miniature and flexible TE power generators for a variety of electronic devices. They also possess intriguing topological phenomena that aim for fascinating applications in low power electronics and quantum computation.